2014
DOI: 10.1007/s12020-014-0336-5
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin D improve liver enzymes, oxidative stress, and inflammatory biomarkers in adults with non-alcoholic fatty liver disease? A randomized clinical trial

Abstract: The aim of this study was to investigate the effects of vitamin D supplementation on serum aminotransferases, insulin resistance, oxidative stress, and inflammatory biomarkers in adult patients with non-alcoholic fatty liver disease (NAFLD). Fifty-three patients with NAFLD were enrolled in a parallel, double-blind, placebo-controlled study. The patients were randomly allocated to receive either one oral pearl consisting of 50,000 IU vitamin D3 (n = 27) or a placebo (n = 26), every 14 days for 4 months. Serum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
144
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(162 citation statements)
references
References 57 publications
10
144
7
1
Order By: Relevance
“…A randomized clinical trial showed that vitamin D reduced serum MDA and liver enzymes, decreased oxidative stress, and reduced the expression of inflammatory biomarkers in adults with NAFLD [29]. In our previous study, the active form of vitamin D down-regulated the NF-κB pathway via Toll-like receptor 4; this was associated with a strong anti-inflammatory effect in rats subjected to liver injury [17].…”
Section: Discussionmentioning
confidence: 83%
“…A randomized clinical trial showed that vitamin D reduced serum MDA and liver enzymes, decreased oxidative stress, and reduced the expression of inflammatory biomarkers in adults with NAFLD [29]. In our previous study, the active form of vitamin D down-regulated the NF-κB pathway via Toll-like receptor 4; this was associated with a strong anti-inflammatory effect in rats subjected to liver injury [17].…”
Section: Discussionmentioning
confidence: 83%
“…In the only published study assessing the direct effects of vitamin D on hepatic steatosis, Sharifi et al [37] recently showed an anti-inflammatory response in NALFD patients. In addition to a weight loss intervention in all patients recommending restriction of high-carbohydrate, high-fat foods and an increase in physical activity, 27 patients received 50,000 IU vitamin D3/biweekly for four months (and 26 received placebo).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies [40][41][42][43], recruited participants with other diseases such as cystic fibrosis, human immunodeficiency virus (HIV), polycystic ovary syndrome and non-alcoholic fatty liver disease. Amongst these studies, one study [41], performed in cystic fibrosis patients, found significant reduction in an inflammatory marker, TNF-α (mean ± SD) 55.67 ± 8.18 pg/ml -27.62 ± 5.82 pg/ml, P < 0.01) ( Table 1).…”
Section: Studies In Participants With Other Conditionsmentioning
confidence: 99%